Using three layer model (TLM) in web form design: WeFDeC checklist development / Zanariah Idrus ... [et al.] - Idrus, Zanariah; Abdul Razak, Nor Hafizah; Abdul Talib, Noor Hasnita; Tajuddin, Taniza (2010)
Since web application forms become as one of the maJor sources m retrieving information especially in e-government system, it is important to design web forms that can give good experiences to users. For the reason, the research presented in this report produced a design checklist (WeFDeC) conforming to task-based form guideline of TLM model, studied how WeFDeC checklist be applied as guidance in designing a better web form and investigate whether the selected local government form conform to WeFDeC checklist. The methodology consists of; develop checklist based on TLM guidelines, select three Malaysia government web forms, validate WeFDeC checklist and compare the forms with WeFDeC checklist. Compared results of pre-test and posttest showed that WeFDeC checklist able to provide guidance in developing web forms. The study on the selected government forms suggests that the forms did not meet TLM model guidelines and need improvement. Continuous studies on the government form could ensure of effectiveness and usableness of the forms. For further work of WeFDeC, the measurement, reliability and effectiveness shall be tested with other web form design checklist and to mobile forms.